Peta Riset Determinan Minat Karier Mahasiswa Akuntansi di Indonesia - Amrie Firmansyah; Andy Setiawan; Dewi Darmastuti (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
This study aims to map the development of the literature on career interest among undergraduate accounting students in Indonesia in pursuing careers as accountants. A scoping review approach was employed to identify the characteristics of existing studies, the professional focus of accounting careers, the methodological approaches adopted, and the main thematic patterns that have emerged in the literature. The literature search was conducted using Publish or Perish with Google Scholar as the primary database, covering articles published between 2016 and 2025. Of the 96 articles initially identified, a systematic screening process involving title and abstract review, followed by full-text assessment, was applied using predefined inclusion and exclusion criteria. As a result, 68 articles were deemed eligible and included in the final scoping review. The mapping results indicate that research on accounting students' career interests in Indonesia predominantly uses quantitative survey methods. Thematically, the literature associates students' career interests with six main groups of factors: economic and financial considerations; labour market conditions and career prospects; professional perceptions and professional recognition; work environment; social influences; and individual or psychological factors. This scoping review provides a comprehensive overview of the directions and trends in research on accounting students' career interest in Indonesia and highlights areas that remain underexplored and warrant further investigation in future studies. Keywords: Career Interest; Accounting Students; Accounting Profession; Indonesia Abstrak Penelitian ini bertujuan untuk memetakan perkembangan literatur mengenai minat karier mahasiswa sarjana dan diploma Akuntansi untuk menjadi akuntan di Indonesia. Penelitian menggunakan pendekatan scoping review untuk mengidentifikasi karakteristik studi, fokus profesi akuntan, pendekatan metodologis, serta tema-tema utama yang berkembang dalam literatur. Penelusuran literatur dilakukan menggunakan perangkat lunak Publish or Perish dengan basis data Google Scholar terhadap artikel yang dipublikasikan dalam rentang waktu 2016-2025. Dari total 96 artikel yang teridentifikasi pada tahap awal, dilakukan proses seleksi melalui screening judul dan abstrak serta penilaian full-text berdasarkan kriteria inklusi dan eksklusi yang telah ditetapkan. Hasil seleksi menunjukkan bahwa sebanyak 68 artikel memenuhi kriteria dan digunakan sebagai dasar pemetaan dalam scoping review ini. Hasil pemetaan menunjukkan bahwa penelitian mengenai minat karier mahasiswa akuntansi di Indonesia didominasi oleh pendekatan kuantitatif berbasis survei. Secara tematik, literatur mengaitkan minat karier mahasiswa dengan enam kelompok faktor utama, yaitu faktor ekonomi dan finansial, pasar kerja dan prospek karier, persepsi profesi dan pengakuan profesional, lingkungan kerja, faktor sosial, serta faktor individual dan psikologis. Pemetaan ini memberikan gambaran komprehensif mengenai arah dan kecenderungan penelitian minat karier mahasiswa akuntansi di Indonesia, sekaligus mengidentifikasi area kajian yang masih relatif terbatas dan berpotensi dikembangkan pada penelitian selanjutnya. Kata Kunci: Minat Karier; Mahasiswa Akuntansi; Profesi Akuntan; Indonesia